The Efficacy Of Anatomical Skeletal System Guidebook For Medical Students At Universitas Jambi - Enis, Rina Nofri; Tarawifa, Susan; Shafira, Nyimas Natasha Ayu; Hz, Tia Wida Ekaputri; Maharani, Citra; Bulqis, Ratu (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACT Background: Medical students need to have good anatomy knowledge. FKIK UNJA changed the learning system to hybrid in response to the COVID-19 pandemic. An update on the skeletal system anatomy practicum guidebook is needed to improve student’s understanding. Objective: This study aims to determine the effect of using the skeletal system anatomy practicum guidebook on the anatomy grade of first-semester students Faculty of Medicine and Health Science Jambi University. Methods: This study applied a quasi-experimental method with a pretest-posttest control group design. The samples were 120 first-semester Jambi University medical students year 2022/2023 who participated in the axial skeleton anatomy practicum. Results: Students with the practicum guidebook pre-test mean grades were (40,58±11,36) and post-test mean grades were (75,74±7,26). Students without practicum guidebook pre-test mean grades were (27,49±13,89) and post-test mean grades were (72,92±5,13). There was a significant difference between the students with and without the practicum guidebook (p-Grades 0,030). Conclusion: The use of the skeletal system anatomy practicum guidebook significantly improves first-semester medical students’ anatomy grades. Keywords: Anatomy Grades, Complete Anatomy, Hybrid, Practicum Guidebook, Skeletal System